Strategi Layanan Digital Dinas PERKIM Provinsi Sumatera Selatan: Analisis Ward and Peppard - Virgie, Marsella; Pratama, Dicky (MDP Student Conference, 2025)
This research examines the strategic planning of Information Systems and Information Technology (IS/IT) at the Housing and Settlement Area Office (PERKIM) of South Sumatra Province using the Ward and Peppard methodology. Although several information systems such as SIPD and SIPPERA PERKIM have been implemented, there are still challenges, such as the lack of system integration and limited digital public services. The research uses Value Chain, PEST, SWOT, and Critical Success Factor (CSF) analysis methods to identify the organization's strategic needs. The analysis results indicate the need for system integration development based on cloud computing and API, as well as the implementation of digital public services using AI chatbots. Strategic recommendations include a 2024-2026 implementation roadmap covering system integration, digital service development, and HR competency enhancement. The implementation of these strategies is expected to improve PERKIM's operational efficiency and public service quality.